Response of human gingival keratinocytes to hybrid CAD/CAM material eluates. Issue 9 (September 2022) - Jennes, Marie-Elise; Tomakidi, Pascal; Husari, Ayman; Hellwig, Elmar; Polydorou, Olga; Schulz, Simon Daniel
Abstract: Objectives: The aim of this study was to investigate the influence of hybrid CAD/CAM-blocks on immortalized human gingival keratinocytes (HGK). Methods: Samples of two different hybrid CAD/CAM materials [Lava™ Ultimate (3 M); VITA Enamic® (VITA Zahnfabrik)], a composite material [ceram.x® universal (Dentsply Sirona)] and a CAD/CAM ceramic [VITABLOCS® (VITA Zahnfabrik)] were stored in cell culture medium for 72 h to prepare eluates according to ISO-10993–12:2012. HGK were exposed to eluates for 6, 24 and 48 h. Cell monitoring was performed by RTCA iCELLigence™ system. The morphological changes were evaluated using phase contrast imaging. Specific biomarkers of apoptosis and terminal differentiation (Caspase-3, Involucrin) were analyzed semi quantitatively by indirect immunofluorescence (IIF). Protein levels and activation of MAP kinases ERK1/2 (p44/42) were quantified by Western blot. Data were statistically analyzed by unpaired t-test (p < 0.05). Results: Regarding Vita Enamic® and Lava™ Ultimate, results of RTCA iCELLigence™ and Western blots showed no statistically significant differences (p > 0.05) compared to the negative control (HGK in native keratinocyte growth medium). No aberrant expression of Caspase-3 and Involucrin was detected in cells incubated with Vita® Enamic eluates Cells incubated with Lava™ Ultimate showed a higher expression of Involucrin after 24 h of incubation compared to the negative control. Statistically significant differences (p < 0.01) were found between cells incubated with ceram.x® universal and the negative control in RTCA iCELLigence™ assay and in quantitative measurements of Western blots after 6 h against phospho-p44/42 (p = 0.044). Increased expression of Caspase-3 and Involucrin were detected by IIF in cells after incubation with eluates of ceram.x® universal. Significance: The present data show no significant effect of hybrid materials on analyzed functions of cell behavior. A cytotoxic influence of ceram.x® universal eluates was observed in HGK in terms of a strong modulation of proliferation, morphology and protein expression. Highlights: Hybrid materials do not influence the cell behavior of HGK. The protein expression of HGK was strongly affected by the composite material. The material composition showed to have a major influence on the cell behavior.